The ethical perplexities of king Ludwig II of Bavaria: madness, extravagance and medical profession - Figueroa, Gustavo (Acta Bioethica, 2021)
1. Bernhard von Guden diagnosed the Bavarian King Ludwig II with “paranoia” (madness), although Ludwig was not personally evaluated by this expert psychiatrist, a diagnosis that the Bavarian government used to justify removing Ludwig from power. 2. His increasingly abnormal behavior, his multiply building projects, for which he incurred much debt, his conviction that he descended from the Bourbons through “baptism”, his unbridled homosexual life, together formed the basis for the psychiatrist´s diagnosis. 3. According to modern criteria of psychiatry Ludwig displayed traits for schizotypal personality disorder together with an orbitofrontal syndrome, and an extravagance way of existence. 4. Bernhard von Gudden based his psychiatric diagnosis and expertise following the ethical principles of beneficence and primum non nocere, “to help, at least not to harm”.